A Captive’s Subjectivity - Blemur, Rebeca J (AUC Knowledge Fountain, 2023)
The project discusses the effects of Haiti’s colonization as the space transitions from Hispaniola to Saint-Domingue and later to the free state of Haiti. This is done by studying the concept of the right to conquest and the absurdities that exist around the first appearances of international law. The project focuses on the pre-revolutionary period starting around the 1750s, the revolutionary period that began in the 1790s, the French oligarchical class’s attempt for social equality, and the war for ultimate colonial conquest between the French, Spanish, and British. The project will display how legally objectifying a human being manifests subjects of the law. This manifestation is challenged by the emergence of the Haitian subject withdrawn from the law or the view of this subject through the medium of warranted violence. As the project begins to discuss the development of the Haitian state and its administration as it maneuvers through notions of legal identity within colonial landscape, it continues to focus on defining subjects of the law. This focus is necessary to formulate a deeper understanding of subjectivity and its effect on the Haitian state. The project will conclude by identifying and defining the Haitian subject and the legal and social infrastructure success of the new Haitian state.